2001
DOI: 10.1038/sj.mp.4000920
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing of the 5-HT2C receptor is reduced in schizophrenia

Abstract: 5-HT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 24 publications
2
126
1
Order By: Relevance
“…Changes in this receptor signaling may be related to the PPI deficit identified in the ADAR2 KO mice. Interestingly, these findings are in accordance with an analogous PPI deficit in schizophrenic patients (32), showing altered editing of the 5-HT2C receptor pre-mRNA in the prefrontal cortex (33). An altered 5-HT2C receptor function might contribute to the hearing deficit in the ADAR2 KO mice, as this receptor is expressed in both the cochlea (34) and inferior colliculus (35).…”
Section: Discussionsupporting
confidence: 73%
“…Changes in this receptor signaling may be related to the PPI deficit identified in the ADAR2 KO mice. Interestingly, these findings are in accordance with an analogous PPI deficit in schizophrenic patients (32), showing altered editing of the 5-HT2C receptor pre-mRNA in the prefrontal cortex (33). An altered 5-HT2C receptor function might contribute to the hearing deficit in the ADAR2 KO mice, as this receptor is expressed in both the cochlea (34) and inferior colliculus (35).…”
Section: Discussionsupporting
confidence: 73%
“…The isoform-dependent constitutive activity could have important implications for the physiological effects of 5-HT by controlling basal tone and sensitivity at synaptic sites. In addition, region-specific generation of edited isoforms (3), coupled with reports of altered RNA editing in suicide (36) and schizophrenia patients (37), suggests that the repertoire of expressed edited 5-HT 2C Rs may contribute to individual differences in brain serotonergic signaling and perhaps even responses to therapeutic agents such as atypical antipsychotic drugs, many of which have been shown to be inverse agonists at the 5-HT 2C R (34,38).…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the idea that trait variation in 5-HT2C-R editing could contribute to differences in stress reactivity in the mouse and, by extension, increase risk for stress-related disorders in the human (Schmauss, 2003). Intriguingly, a number of studies have found increased 5-HT2C-R editing in the mPFC of schizophrenics and depressive suicides (Gurevich et al, 2002;Sodhi et al, 2001). There is also preliminary evidence that structural variants in the human HTR2C gene, including a Cys23Ser SNP, are associated with bipolar disorder and major depression (Lappalainen et al, 1999;Lerer et al, 2001;Massat et al, 2007).…”
Section: -Ht2c Receptorsmentioning
confidence: 99%